2022
DOI: 10.3390/molecules27238249
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiles, Antioxidant, Cytotoxic, and Anti-Inflammatory Activities of Traditional Medicinal Plants: Centaurea pichleri subsp. pichleri, Conyza canadensis, and Jasminum fruticans

Abstract: Centaurea pichleri subsp. pichleri, Conyza canadensis, and Jasminum fruticans are traditionally used plants grown in Turkey. Methanol extracts were obtained from these plants and pharmacological activity studies and phytochemical analyses were carried out. To evaluate the phytochemical composition, spectrophotometric and chromatographic techniques were used. The extracts were evaluated for antioxidant activity by DPPH●, ABTS●+ radical scavenging, and FRAP assays. The cytotoxic effects of the extracts were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
0
1
Order By: Relevance
“…Few studies reported the TPC and TFC for the methanolic plant extract of C. canadensis. The TPC and the TFC of C. canadensis from Moroccan origin [27] (2.54 µg /mg DM and 19.31 µg/mg DM, respectively) and Turkish origin [28] (71.34 ± 0.53 mg GAE/g extract; 18.91 ± 1.46 mg CA/g extract, respectively) were lower than those detected in our current investigation. Also, the observed DPPH radical scavenging power in our current study was higher than those observed in previous reports [20,27,28].…”
Section: Tpc Tfc Dpph Scavenging and Iron Chelating Activity For Ccm ...contrasting
confidence: 89%
“…Few studies reported the TPC and TFC for the methanolic plant extract of C. canadensis. The TPC and the TFC of C. canadensis from Moroccan origin [27] (2.54 µg /mg DM and 19.31 µg/mg DM, respectively) and Turkish origin [28] (71.34 ± 0.53 mg GAE/g extract; 18.91 ± 1.46 mg CA/g extract, respectively) were lower than those detected in our current investigation. Also, the observed DPPH radical scavenging power in our current study was higher than those observed in previous reports [20,27,28].…”
Section: Tpc Tfc Dpph Scavenging and Iron Chelating Activity For Ccm ...contrasting
confidence: 89%